2004
DOI: 10.1002/ejoc.200300338
|View full text |Cite
|
Sign up to set email alerts
|

A New Route to Protected Acyloins and Their Enzymatic Resolution with Lipases

Abstract: A series of 16 different 3-acyloxy methyl ketones, the acyloin acetates and butyrates (±)-5, was synthesised by a straightforward new method through alkylation of tert-butyl 2-acyloxyacetoacetates 3, followed by chemoselective dealkoxycarbonylation of the tert-butyloxycarbonyl group in the presence of other ester groups. Subsequent hydrolysis of (±)-5 can be achieved with base to give racemic acyloins 6, or with lipase catalysis to afford the corresponding non-racemic acyloins (S)-6. The remaining (R)-acyloin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 43 publications
6
45
0
Order By: Relevance
“…For example, they have been employed in the synthesis of different pharmaceuticals [75][76][77], and can be easily transformed into the corresponding α-hydroxy ketones, which are structural units present in a large variety of biologically active molecules [78,79]. Among the different synthetic approaches to β-oxo esters [80], the ruthenium-catalyzed addition of carboxylic acids to terminal propargylic alcohols has emerged Scheme 22.…”
Section: Catalytic Addition Of Carboxylic Acids To Terminal Propargylmentioning
confidence: 99%
“…For example, they have been employed in the synthesis of different pharmaceuticals [75][76][77], and can be easily transformed into the corresponding α-hydroxy ketones, which are structural units present in a large variety of biologically active molecules [78,79]. Among the different synthetic approaches to β-oxo esters [80], the ruthenium-catalyzed addition of carboxylic acids to terminal propargylic alcohols has emerged Scheme 22.…”
Section: Catalytic Addition Of Carboxylic Acids To Terminal Propargylmentioning
confidence: 99%
“…Wessjohann and co-workers reported [16] a kinetic resolution of rac - 3 f using amano lipase PS from Burkholderia capacia , which worked smoothly on gram-scale to provide both the starting material and product in greater than 99:1 e.r. Since the stereochemistry at C4 is unknown, access to both diastereomers of the alkene ( 3h and 3i ) was necessary.…”
mentioning
confidence: 99%
“…17 However, while condensation of this reagent with commercial 6-methyl-5-hepten-2-one gave the THP derivative of compound 8 as a 1.4:1 mixture of Z - and E -olefin isomers, those isomers were not readily separated either as the THP acetals or as the free alcohols. 15 There are several reports on preparation of homonerol and homogeraniol 1719 or the corresponding carboxylic acids, 20 but to secure pure samples of the individual isomers a new sequence derived from research reported by Wessjohann and co-workers 21 appeared to be particularly attractive (Scheme 1). Their strategy relied upon classical acetoacetate chemistry and recently was employed in a clever synthesis of epothilone D. 22 For that effort, the Z stereochemistry of a trisubstituted olefin was derived from neryl bromide and cleanly preserved throughout their reaction sequence.…”
mentioning
confidence: 99%
“…21 Hydrolysis of this acetate proceeded smoothly to the acyloin 12 , 23 but then our efforts to bring about oxidative cleavage to the carboxylic acid went unrewarded. In contrast, reduction of compound 11 proceeded smoothly upon treatment with LiAlH 4 to give the diol 13 as a mixture of stereoisomers, and oxidative cleavage by treatment with sodium periodate on silica gel gave the expected aldehyde 14 in nearly quantitative yield.…”
mentioning
confidence: 99%